San Jose Safe Deposit Bank building ornament - Gordon, John C. (photographer):::Creator::::::::::::
Building ornament that sat at the top of the San Jose Safe Deposit Bank building. At the top of the ornament is a bird with its wings spread open. Two bears are at opposing sides below the bird and in between the bears is the year "1872". The word "Bank" appears at the bottom of the ornament.